Praktik Yoga Arsitek Bade: Membaca Praktik Yoga Penglukunan Dasa Aksara Undagi Bade - I Putu Gede Suyoga (UHN IGB Sugriwa Denpasar, 2018)
Every profession has the realm of yoga applications that are relevant to the practice of their profession. An undagi “architect” in addition to equipping himself with design skills and technical skills for “artifacts”, is alsoobliged to master the mind (yoga), one of which is the literacy technique “union of ten scripts / holy letters”.This study aims to uncover the phenomenon of undagi bade which is able to capture the knowledge behind thescript as a practice of yoga for spiritual practice, and manifested in the form of bade architectural artifacts.This study is a qualitative study with a descriptive analytical approach. Collecting data by observation anddocumentation. Determination of informants is done by purposive sampling. Data analysis was based onMichel Foucault’s knowledge power relations theory. The results of the study showed that the architecture ofthe bade was composed of pepalihan (parts) that compose parts of the body and roof. The shape varies thereare those who are not overlapping called a container and whose roof is overlapped is called a bade, some evenhave no roof (open) called padma. This roof variant is the result of a deep contemplation of “yoga” literacy.Knowledge of the dasa aksukan capturing was captured by undagi bade to be developed as power in the practice of his profession. This power of knowledge practice applies in the realm of Balinese society whose bodieshave been disciplined, obedient and useful in carrying out ceremonial cultural practices of death. Personallythe meaning of yoga in literacy is the practice of training the undagi self-discipline in seeking authenticity onthe path of Tantra.